2022
DOI: 10.3389/fpls.2022.828153
|View full text |Cite
|
Sign up to set email alerts
|

Increased sulfur-containing amino acid content and altered conformational characteristics of soybean proteins by rebalancing 11S and 7S compositions

Abstract: Soybean proteins are limited by their low contents of methionine and cysteine. Herein, 7S globulin accumulation was reduced using RNA interference to silence CG-β-1 expression, and the content of the A2B1a subunit was largely increased under the soybean seed-specific oleosin8 promoter. The results showed that the sulfur-containing amino acid content in soybean seeds drastically improved, reaching 79.194 nmol/mg, and the 11S/7S ratio had a 1.89-fold increase compared to the wild-type acceptor. The secondary str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…According to previous studies, 11S globulin has been found to be rich in sulfur-containing amino acids, with a content that is five to six times higher than that of 7S globulin. This indicates that 11S globulin has higher protein quality and can provide greater nutritional value [57].…”
Section: Sds-page Analysismentioning
confidence: 99%
“…According to previous studies, 11S globulin has been found to be rich in sulfur-containing amino acids, with a content that is five to six times higher than that of 7S globulin. This indicates that 11S globulin has higher protein quality and can provide greater nutritional value [57].…”
Section: Sds-page Analysismentioning
confidence: 99%
“…Soybean is an indispensable raw material in animal feed due to its high protein content, high protein digestibility, balanced amino acid composition, availability, and relatively fair production cost. Generally speaking, soybean seeds contain 35–40% protein [ 88 ], with the storage proteins 11S globulin and 7S globulin accounting for 70–80% of the total protein [ 89 ]. The total protein content of rice seeds is only about 8%, which is one of the crops with the lowest protein content.…”
Section: Gene Resources and Strategies For Crop Nutrient And Quality ...mentioning
confidence: 99%
“…Reports indicate that a deficiency in these amino acids can negatively impact animal growth and development. 23 Plant proteins, such as pea, 24 soybean, 23,25 almond 26 and chickpea protein 27 are particularly deficient in these amino acids. Hemp protein is of interest as it is rich in cysteine and methionine.…”
Section: Introductionmentioning
confidence: 99%